The impact of firm size on pay–performance sensitivities - Cichello, Michael S. (Journal of Corporate Finance, 2005)
Previous work by Aggarwal and Samwick [Aggarwal, R., Samwick, A., 1999. The other side of the tradeoff: the impact of risk on executive compensation. Journal of Political Economy 107 pp. 65–105] has documented the importance of controlling for the variance of firm stock returns when estimating pay–performance sensitivities. They find that pay–performance sensitivities are an order of magnitude greater for small vs. large variance firms. Using a comparable sample of CEOs, I provide evidence that when properly controlling for firm size, the negative effect of variance in stock returns on estimated pay–performance sensitivities is greatly diminished. In particular, when using dollar returns as the measure of firm performance, it is imperative to properly control for firm size.